Intergenerational education as a strategy for promoting active ageing - Villas-Boas, Susana (2019)
The objective of this article is to present the main results of a study about intergenerational education as a strategy for promoting active ageing. The research took place in the parish of Bonfim, Oporto city, Portugal, and involved a sample of 385 residents, divided into three age groups (young-adults, middle-aged adults and older adults). The data came from the Questionnaire for Assessing Needs, Interests and Potentials for the Development of Intergenerational Programs, from which the following variables were considered: social participation; leisure activities; social support and quality of life. As main results, one can point that older subgroups show less social participation and leisure activities, low social support networks and also low quality of life compared to younger subgroups. A gender effect was also noticed, since the social roles performed across adulthood by man and women result in less social participation of women, less leisure activities, less social support networks and a worse evaluation of their quality of life.